Temperature dependence of anisotropic magneto-Seebeck effect in NiPt alloys. (7th June 2021) - Hirai, Takamasa; Modak, Rajkumar; Miura, Asuka; Seki, Takeshi; Takanashi, Koki; Uchida, Ken-ichi
Abstract: This letter reports systematic measurements of the anisotropic magneto-Seebeck effect (AMSE) of ferromagnetic Ni100− x Pt x alloys with different Pt concentration ratios x . By simultaneously measuring an applied temperature difference and generated thermopower at the same positions, the Seebeck coefficient under a magnetic field is quantified with high reliability at the temperatures ranging from 300 to 550 K. The AMSE of the alloys is maximized at around x = 5 at% in the high temperature range and disappears at the temperatures lower than the Curie temperature. The systematic dataset and experimental techniques established here will invigorate spin caloritronics studies.